Untangling research and practice: What Facebook's "emotional contagion" study teaches us. (January 2016) - boyd, danah
Published in 2014, the Facebook "emotional contagion" study prompted widespread discussions about the ethics of manipulating social media content. By and large, researchers focused on the lack of corporate institutional review boards and informed consent procedures, missing the crux of what upset people about both the study and Facebook's underlying practices. This essay examines the reactions that unfolded, arguing the public's growing discomfort with "big data" fueled the anger. To address these concerns, we need to start imagining a socio-technical approach to ethics that does not differentiate between corporate and research practices.